2010
DOI: 10.1128/iai.01056-09
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Resistance to Complement-Mediated Immunity Is Dependent on the Capsular Serotype

Abstract: Streptococcus pneumoniae strains vary considerably in the ability to cause invasive disease in humans, and this is partially associated with the capsular serotype. The S. pneumoniae capsule inhibits complement-and phagocyte-mediated immunity, and differences between serotypes in these effects on host immunity may cause some of the variation in virulence between strains. However, the considerable genetic differences between S. pneumoniae strains independent of the capsular serotype prevent an unambiguous assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
111
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 47 publications
8
111
2
Order By: Relevance
“…We found that complement deposition on pneumococci correlates with the anticapsular antibody concentration required for opsonophagocytic killing: the serotypes that were least resistant to C3 deposition required the lowest concentration of capsule antibodies. TIGR4 serotypes 4 and 7F have previously been reported to be more resistant to C3 deposition than serotypes 6A and 23F (16), whereas in the present study TIGR4 serotype 4 was less resistant than 23F. Since the mutants of these two studies were constructed independently, the source of the TIGR4 parent strain (serotype 4) could affect the results.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…We found that complement deposition on pneumococci correlates with the anticapsular antibody concentration required for opsonophagocytic killing: the serotypes that were least resistant to C3 deposition required the lowest concentration of capsule antibodies. TIGR4 serotypes 4 and 7F have previously been reported to be more resistant to C3 deposition than serotypes 6A and 23F (16), whereas in the present study TIGR4 serotype 4 was less resistant than 23F. Since the mutants of these two studies were constructed independently, the source of the TIGR4 parent strain (serotype 4) could affect the results.…”
Section: Discussioncontrasting
confidence: 52%
“…Although nonopsonic phagocytic receptors can mediate phagocytosis directly (51), neutrophil phagocytosis is markedly increased by opsonization of pneumococcus with complement (56). Complement deposition on TIGR4 mutants expressing different serotypes correlated with neutrophil phagocytosis in the presence of complement, but differences in phagocytosis between strains were abolished when the bacteria were not opsonized with complement (16). We found that complement deposition on pneumococci correlates with the anticapsular antibody concentration required for opsonophagocytic killing: the serotypes that were least resistant to C3 deposition required the lowest concentration of capsule antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these characteristics might partly be related to the expression of a non-pore-forming PLY, the overall characteristic of a given pneumococcal type (colonizer/cause of invasive disease) is certainly the sum of different features and clearly depends on variations of other bacterial factors including the capsular polysaccharides (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Amount and composition of polysaccharide capsule expression is used to distinguish between up to 94 pneumococcal serotypes (oral communication with Dr. M. van der Linden, NRZ Aachen). Each serotype is characterized by an individual polysaccharide capsule, which mediates the escape from phagocytosis or complement factor binding and prevents entrapment by neutrophil extracellular traps [9][10][11][12][13]. The predominant serotypes associated with severe pneumococcal diseases vary with respect to geographical and demographical situation and respective vaccination programs.…”
Section: Introductionmentioning
confidence: 99%